ANALYZING THE RELATION BETWEEN LEARNER CLASS PARTICIPATION AND ENGLISH-SPEAKING PROFICIENCY - Marsella, Elisabeth; Dewi, Ratna Mustika (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2025)
Non-English major students often face problems in practicing speaking English due to their reluctance. To overcome this, participation scores are used to motivate learners to participate in class discussions. Therefore, this study examines the relationship between learners' participation scores and their English-speaking proficiency. To answer the question, this study implements a quantitative method by collecting learners' participation scores and speaking proficiency. Additionally, data on learners' gender and attendance were included to examine the correlation. The data were collected from 255 students majoring in Information Systems who enrolled in the English for Business Communication class during the academic years 2022–2024. The finding shows that gender has a weak correlation with learners' speaking proficiency. Meanwhile, attendance and participation scores show a positive correlation at the medium level with learners' speaking proficiency.